Politicization and institutional (non-) change in international taxation; Politisierung und institutioneller (Nicht-)Wandel des internationalen Steuerregimes - Thomas Rixen (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2008)
This paper explores the institutional changes of international tax governance in response to growing politicization and contestation of international direct tax issues. I show that politicization – which is a very recent phenomenon in international taxation – results from a governance gap. The traditional setup of international tax cooperation has an unintended consequence in the form of harmful tax competition. In reaction to this problem, civil society groups have begun to question the effectiveness and fairness of the minimal international tax order, lobbying national governments and international organizations for more effective international regulation of tax issues. Thus, in contrast to existing hypotheses, societal politicization does not result from the increasing scope and authority of international institutions, but rather from the lack thereof. However, civil society demands have so far not led to institutional changes in international taxation. Instead, we can only observe indirect and incremental change, which falls short of what would ultimately be needed to address harmful tax competition effectively. – – Dieses Papier untersucht den institutionellen Wandel des internationalen Steuerregimes in Reaktion auf eine zunehmende Politisierung internationaler Steuerangelegenheiten. Gesellschaftliche Politisierung, die im Bereich der internationalen Besteuerung ein sehr junges Phänomen ist, hat ihre Ursache in einer Governancelücke. Das traditionelle institutionelle Arrangement zur Vermeidung von internationaler Doppelbesteuerung hat nicht-intendierte Nebenfolgen in der Form von schädlichem und unfairem Steuerwettbewerb. Als Reaktion auf dieses Problem haben zivilgesellschaftliche Akteure den Mangel an Effektivität und Fairness skandalisiert. Sie versuchen nationale Regierungen und internationale Organisationen zu mehr internationaler Regulierung des Steuerwettbewerbs anzutreiben. Anders als in Teilen der Literatur angenommen wird, ist die gesellschaftliche Politisierung nicht das Resultat eines Zuwachses an politischem Einfluss von nicht ausreichend legitimierten internationalen Institutionen, sondern sie thematisiert im Gegenteil den Mangel an effektiven internationalen Institutionen. Die zivilgesellschaftlichen Forderungen haben bisher nicht zu institutionellen Reformen geführt. Stattdessen lässt sich lediglich indirekter und inkrementeller Wandel beobachten, der nicht ausreichend ist, um das Problem schädlichen Steuerwettbewerbs zu lösen.
Keywords: 300